AKUNTABILITAS KINERJA PEGAWAI DALAM PELAYANAN PUBLIK DI KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Andi Pattarani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
This study aims to 1) describe and analyze the professionalism of the apparatus of the District of North Luwu Regency in carrying out the duties and functions of the organization professionally, especially from the aspect of responsiveness and innovation, 2) analyze what factors are faced and affect the Masamba District of North Luwu Regency in developing the apparatus. professional in terms of responsiveness and innovation in carrying out the duties and functions of the organization. This study uses a qualitative descriptive method. With data analysis techniques, namely: data reduction, data organization, and interpretation. The results of the study indicate that 1) The responsiveness and innovation of the Masamba District apparatus both in the context of serving the community and in carrying out other tasks are considered lacking, so that the noble goals of the organization and providing the best services for the community have not been achieved; 2) The vision and mission of the organization is limited to being a decoration of the cabinets and walls of the Masamba District Office; 3) The authorities and responsibilities of each Masamba District apparatus have been well understood and implemented from the top leadership (Camat), middle officials (Sekcam and Section Heads) to the implementing staff although they still use a hierarchical system in carrying out tasks and making decisions; 4) The leadership of the Masamba Camat in managing the administration and managing the running of the organization can be said to have gone quite well where in addition to using a formal approach, the Camat also uses an informal approach so that there is an emotional closeness with his subordinates; 5) The awards received, especially financial awards based on seniority of service period and meritocracy, are still considered inadequate and do not reflect justice by several Masamba District employees; 6) Another factor that has a considerable influence on the professionalism of the apparatus is seen from the responsiveness and innovation of the government apparatus in Masamba District, namely the organizational culture that grows and continues to develop.